2009
DOI: 10.1038/sj.bjc.6604886
|View full text |Cite
|
Sign up to set email alerts
|

LKB1/KRAS mutant lung cancers constitute a genetic subset of NSCLC with increased sensitivity to MAPK and mTOR signalling inhibition

Abstract: LKB1/STK11 is a multitasking tumour suppressor kinase. Germline inactivating mutations of the gene are responsible for the PeutzJeghers hereditary cancer syndrome. It is also somatically inactivated in approximately 30% of non-small-cell lung cancer (NSCLC). Here, we report that LKB1/KRAS mutant NSCLC cell lines are sensitive to the MEK inhibitor CI-1040 shown by a dose-dependent reduction in proliferation rate, whereas LKB1 and KRAS mutations alone do not confer similar sensitivity. We show that this subset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 22 publications
8
86
0
1
Order By: Relevance
“…Once the LKB1 gene is mutated, metformin may only inhibit proliferation by downregulating MAPK. These observations are consistent with previous studies (31)(32)(33).…”
Section: Discussionsupporting
confidence: 94%
“…Once the LKB1 gene is mutated, metformin may only inhibit proliferation by downregulating MAPK. These observations are consistent with previous studies (31)(32)(33).…”
Section: Discussionsupporting
confidence: 94%
“…Coexisting STK11/LKB1 and KRAS mutations sensitize NSCLC cells to either mTOR or MEK inhibition (18), and evidence from xenograft experiments also supports the use of dual PI3K/mTOR inhibition in this context (4). Mouse models have demonstrated that LKB1 loss can also cooperate with PTEN loss to drive the tumorigenesis of a (19).…”
Section: Tumors With Stk11/lkb1 Alterationsmentioning
confidence: 88%
“…Nearly one-third of NSCLC samples harbor inactivating alterations of STK11/LKB1 (16), which are known to frequently coexist with KRAS mutations, and are thought to play an important role in progression to metastasis (17,18). Coexisting STK11/LKB1 and KRAS mutations sensitize NSCLC cells to either mTOR or MEK inhibition (18), and evidence from xenograft experiments also supports the use of dual PI3K/mTOR inhibition in this context (4).…”
Section: Tumors With Stk11/lkb1 Alterationsmentioning
confidence: 99%
“…LKB1 was first recognized as a tumor-suppressor gene because its mutations cause Peutz-Jeghers syndrome, characterized by gastrointestinal hamartoma with an increased cancer risk (Giardiello et al, 2000;van Lier et al, 2010). This gene was later found to be a target for mutational inactivation in human malignancies including non-small cell lung carcinoma (Sanchez-Cespedes et al, 2002;Carretero et al, 2004;Ji et al, 2007;Matsumoto et al, 2007;Makowski and Hayes, 2008;Komiya et al, 2010;Mahoney et al, 2009), cervical carcinoma (Wingo et al, 2009), melanoma (Guldberg et al, 1999;Rowan et al, 1999) and others (Sanchez-Cespedes, 2007). The LKB1 gene encodes a serine/threonine kinase essential for the activation of AMPK (AMP-activated protein kinase) and 12 AMPK-related kinases; thus, it regulates multiple signaling pathways in cell growth, cell polarity and metabolism (Hezel and Bardeesy, 2008;Shackelford and Shaw, 2009;Luo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%